SwedeAmp—the Swedish Amputation and Prosthetics Registry: 8-year data on 5762 patients with lower limb amputation show sex differences in amputation level and in patient-reported outcome - Kamrad, Ilka; Söderberg, Bengt; Örneholm, Hedvig; Hagberg, Kerstin (Acta Orthopaedica, 2020)
Background and purpose — For want of national guidelines for lower limb amputation (LLA) the quality registry SwedeAmp was started in 2011 to increase knowledge around LLA and prosthetic rehabilitation. We now present data from the first 8 years of registration. Patients and methods — We present descriptive data from the first 8 years (2011–2018) of registration. Patientreported outcome was collected at baseline and at follow-up 12 and 24 months after surgery for patients with prosthetic supply and included generic (EQ-5D-5L) and amputee-specific (e.g., LCI-5L and Prosthetic Use Score) measures. Sex differences were investigated. Results — As at December 31, 2018, 5,762 patients, 7,776 amputations, 2,658 prosthetic supplies, 1,848 baselines, and 2,006 follow-ups were registered. 61% of the patients were male, and mean age by the time of the first registered amputation was 74 years (SD 14). Women were older, more frequently had vascular disease without diabetes and more often underwent amputation at a higher level compared with men (p < 0.001). Time from amputation to fitting of first individual prosthesis was median 69 days (6–500) after transtibial amputation (TTA) and 97 days (19–484) after transfemoral amputation (TFA). The outcomes were lower after TFA than after TTA. Interpretation — SwedeAmp shows sex differences concerning amputation level, diagnosis, and age, leading to the conclusion that women have worse preconditions for successful prosthetic mobility after LLA. With increasing coverage, SwedeAmp can provide deeper knowledge with regard to patients undergoing LLA in Sweden.